Skema Penerapan Unexplained Wealth: Reformulasi Perampasan Aset pada Tindak Pidana Korupsi di Indonesia - Mahdi, Wahyu Laksana; Garini, Meza Rahmada; Azzahra, Carissa Ivadanti (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2022)
Abstract: The criminal act of corruption has developed as an extraordinary crime. Corruption eradication regulations in Indonesia still focus on non-asset so that they have not been effective in suppressing corruption crimes. The authors uses a normative juridical research with a statutory approach. The government's efforts to confiscate the assets of criminal acts of corruption have two mechanisms, namely criminal and civil in Law No. 8 of 1981 concerning Criminal Procedure Law, Law No. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, as well as Law No. 7 of 2006 concerning Ratification of the United Nations Convention Against Corruption. The regulation does not yet have a comprehensive framework. Therefore, unexplained wealth as a mechanism for confiscating assets to optimize actions in criminal acts of corruption. There are three implementations of unexplained wealth. First, renewal of legal products, namely the Draft Law on Confiscation of Criminal Acts of Assets, especially corruption. Second, law enforcement officials are guided by the regulations that have been drafted in the Asset Confiscation Draft. Third, the proof mechanism uses reverse proof. Keywords: Asset Confiscation, Corruption, Mechanism, Scheme, Unexplained Wealth.